Principles and Strategies of Water Security in Islamic Law: an Analytical Study in the Methodology of Application | مبادئ واستراتيجيات الأمن المائي في الشريعة الإسلامية: دراسة تحليلية في منهجية التطبيق - Baidar Mohammed Mohammed Hasan; Muneer Ali Abdul Rab; Hasnizam b Hashim; Mualimin Mochammad Sahid (Al-Zahra : Journal for Islamic and Arabic Studies, 2021)
The study aimed at “Principles and Strategies of Water Security in Islamic Sharia Analytical Study in the Application Methodology” to present the philosophy of the basic principles of water security in Islamic Sharia according to data based on a Muslim fact, which is that water security is a solid foundation for food security for humanity, and in light of that, it requires a study of the principles The main and basic principles of water security in Islamic law, given that achieving the principles of water security in practice is the correct and sound strategy in the way of achieving food security, and accordingly, the research will address the issue by dividing the study into three main axes and a conclusion, and the first axis will include existential principles of water security in Islamic law, and in the second axis, the study will discuss the methodological principles of water security in Islamic law. In the third axis, the study will propose some strategic mechanisms that guarantee the achievement of water security in accordance with the legislative interests indicated by the Sharia texts. Consumption of water resources, development and development of water resources, and preservation from pollution, and water security in Islamic law has existential sources, represented in the importance of water security for food security and human partnership in water resources, and this is what makes it imperative for people as partners in water resources to be partners In achieving water security, which is the basis for achieving food security. And that the Islamic Sharia has made practical contributions to its application, represented in rationalizing the consumption of water resources, developing and preserving them from pollution in all its forms and types.